The demand and supply of trans-oceanic sea routes: the case of East Asia-US east coast container trade. Issue 3 (2016) - Pagano, Anthony M.; Zou, Bo; Sánchez, Onésimo V.; Noruzoliaee, Mohamadhossein
The Panama Canal expansion will create a new lane of traffic for larger ships, up to 13, 000-14, 000 TEUs. While trade between Asia and the USA continues to increase, a number of supply factors may impact the canal's position. First, several US and Canadian west coast ports plan to increase service levels. Second, railroads serving the US west coast are examining the possibility of lowering freight rates. Third, the Nicaragua Grand Canal has been proposed and started construction. Fourth, the Suez Canal is expanding operations and may capture some of the traffic currently transiting the Panama Canal. Fifth, multiple Central American countries are considering constructing 'dry canal' rail links between the Pacific and Caribbean coasts. These together may result in an excess supply of trans-oceanic sea services. This paper examines the possible changes in supply and demand with emphasis on East Asia-US container trade.